2014
DOI: 10.1094/phyto-07-13-0210-r
|View full text |Cite
|
Sign up to set email alerts
|

History of Oilseed Rape Cropping and Geographic Origin Affect the Genetic Structure ofPlasmodiophora brassicaePopulations

Abstract: The soilborne pathogen Plasmodiophora brassicae causes clubroot on Brassica crops, a common disease in many oilseed rape growing regions. Here, we investigate genetic diversity and geographic differentiation of P. brassicae populations from different regions in Germany. We compared three regions that differ in oilseed rape cropping history, oilseed rape acreage, and incidence of clubroot. These regions were either spatially separated or separated by the former inner German border. Plasmodiophora isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
1
12
0
1
Order By: Relevance
“…(), who classified collected German isolates as P1, P3 and P6, respectively. Moreover, the diversity of virulence found in different areas of Germany, observed in the present study, is in close agreement with the degree of genetic variation found in the P. brassicae populations identified using AFLP, in which every field isolate showed a unique genotype pattern (Strehlow et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…(), who classified collected German isolates as P1, P3 and P6, respectively. Moreover, the diversity of virulence found in different areas of Germany, observed in the present study, is in close agreement with the degree of genetic variation found in the P. brassicae populations identified using AFLP, in which every field isolate showed a unique genotype pattern (Strehlow et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These results suggested that the investigated field isolates are genetically uniform and stable, although we cannot exclude a possibility that one pathotype might be dominant and others might be present at a low frequency and easily overlooked. Strehlow et al (2014) presented that the 59 field isolates exhibited a unique genotype pattern depending on the regions or fields. The authors proposed that the geographic differentiation resulted from low levels of gene flow due to the limited dispersal of the soilborne pathogen P. brassicae and from the localized selection pressure as a unifying force on the genotypes of the host (Strehlow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Strehlow et al (2014) presented that the 59 field isolates exhibited a unique genotype pattern depending on the regions or fields. The authors proposed that the geographic differentiation resulted from low levels of gene flow due to the limited dispersal of the soilborne pathogen P. brassicae and from the localized selection pressure as a unifying force on the genotypes of the host (Strehlow et al, 2014). Thus, the collection and characterization of field isolates showing different pathogenicities would be useful for breeding of CR Chinese cabbage.…”
Section: Discussionmentioning
confidence: 99%
“…Dennoch konnten unsere Untersuchungen zeigen, dass Sandgehalte von 30 bis 35 % und niedrige Boden-pH-Werte von unter 5,6 auf Praxisschlägen mit einem hohen Kohlherniebefall korrelieren. tisch sehr unterschiedlich sind (Strehlow et al 2014), was mit einer fehlenden Vermischung der Feldisolate durch Verschleppung verseuchter Erde begründet wurde.…”
Section: Diskussionunclassified